Social potential of youth: theoretical and methodological bases of research - Chernyak, Yuri G. (Journal of the Belarusian State University. Sociology, 2019)
The article presents the theoretical substantiation of the concept of «social potential». Features of forming the social potential of young people, factors and conditions affecting its implementation, as well as the reasons for changing the qualitative characteristics of representatives of the younger generation are considered. The necessity of sociological study of social potential of youth is substantiated. The importance of his research in the practice of social management is determined.
Keywords: youth; social potential; social development